2013
DOI: 10.1111/jgh.12184
|View full text |Cite
|
Sign up to set email alerts
|

Size and type of periampullary duodenal diverticula are associated with bile duct diameter and recurrence of bile duct stones

Abstract: PAD are associated with larger CBD stones and severe cholangitis with CBD stones. CBD diameter is related to PAD size, and the recurrence of CBD stones is related to PAD type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 22 publications
4
47
1
Order By: Relevance
“…PAD is a risk factor for CBD stone formation that often causes a dilated CBD [21] that may affect the function of the SO [22]. In our study, about 36.8% (28/76) patients were with PAD, and this is similar to the result of a recent study from South China that the percentage is 38.8% (99/255) [23].…”
Section: Discussionsupporting
confidence: 89%
“…PAD is a risk factor for CBD stone formation that often causes a dilated CBD [21] that may affect the function of the SO [22]. In our study, about 36.8% (28/76) patients were with PAD, and this is similar to the result of a recent study from South China that the percentage is 38.8% (99/255) [23].…”
Section: Discussionsupporting
confidence: 89%
“…Also periampullary diverticuli are associated with larger stones and severe cholangitis [15, 16]. This could not be confirmed in the present study; stones in the common bile duct as well as cholangitis occurred in both groups of patients.…”
Section: Discussioncontrasting
confidence: 75%
“…However, only a small number of patients in this series (27 patients) had PAD and age was not adjusted in the control group. The most recent study by Kim et al 16 has suggested that there is an association between large PAD and dilated CBD based on a total of 74 cases. Similar to the previous studies, age was not matched in the control group.…”
Section: Discussionmentioning
confidence: 99%